Evaluation of Internal Control Activities and their Role in Administrative Decisions - محمد طارق عبد الستار; محمد اياد طاهر (Journal of Economics and Administrative Sciences, 2020)
The current research aims to verify the relationship and impact of internal control activities as an independent variable in its dimensions (efficiency, training, independence) in making administrative decisions as a responsive variable and its dimensions (identifying and diagnosing the problem, searching for alternatives, evaluating alternatives, choosing the appropriate alternative, implementing the decision, following up Decision and evaluation) in the Kirkuk Water Directorate, as well as to identify the levels of their practices, and then try to come up with a number of recommendations contribute to the strengthening of internal control activities and the process of making administrative decisions of the researched Directorate, and proceeding from the importance of the subject of research in public service organizations, and Its importance to the research department and to the community, The methodology was adopted by the case study in the completion of this research, and data were collected from (52) respondents representing the research community exclusively and comprehensively, represented by (Director General, Assistant Director General, heads of departments and divisions), using the questionnaire which included (51) paragraphs, and used interviews And field observations as methods to assist in their collection. The research adopted the program (Amos V.23, Spss V.23) with the adoption of descriptive statistical methods (natural distribution test, empirical factor analysis, modeling of variables, arithmetic mean, percentages, standard deviation, relative importance, coefficient of variation, Pearson correlation coefficient, Simple regression coefficient, and multiple regression coefficients) to test its hypotheses, The research concluded to the most prominent conclusion, which showed the validity of the hypotheses and reflected the existence of good interrelationships between internal control activities and administrative decision-making process, which made management control activities influential in the process of administrative decision-making in the Kirkuk Water Directorate, as well as the emergence of efficiency and independence more influential in the process Making administrative decisions.